Pengaruh Takaran Kompos Biochar Pupuk Kandang Sapi terhadap Pertumbuhan Beberapa Kultivar Kacang Hijau (Vigna radiata L.) - Maria Afnita Lelang; Vasco Gusmao (Savana Cendana, 2019)
This study aims to determine the response of green bean cultivars to the application of biochar compost and the effect of biochar compost dosage on the growth and yield of green beans and the best dosage of biochar compost on the growth and yield of green beans, yellow beans and black beans. This study used a 4 × 3 factorial randomized block design that was repeated 3 times. The first factor is the dosage of biochar compost for cow manure which consists of 4 levels, namely control 0 t/ha, 10 t/ha, 15 t/ha, 20 t/ha the second factor is the type of green beans consisting of local green beans Timor Fore Belu, beans Black and yellow beans, which were repeated 3 times so that there were 36 treatment units. The parameters observed in this study are environmental parameters, growth parameters and yield parameters. The results showed that there was no interaction between the biochar compost dosage treatment with the type of bean on all observational parameters except for the observation parameters of plant height 21 days, root length 35 days, total root nodules 50 days, and number of pods per plant. Compost biochar affects the growth and yield of green beans. Types of green beans affect the growth and yield of plants. The best dose for the type of green bean speckle is 20 t/ha, yellow is 15 t/ha, black is 15 t/ha.